2019
DOI: 10.1038/s41598-019-54278-9
|View full text |Cite
|
Sign up to set email alerts
|

Monocrystalline Silicon Carbide Disk Resonators on Phononic Crystals with Ultra-Low Dissipation Bulk Acoustic Wave Modes

Abstract: Micromechanical resonators with ultra-low energy dissipation are essential for a wide range of applications, such as navigation in GPS-denied environments. Routinely implemented in silicon (Si), their energy dissipation often reaches the quantum limits of Si, which can be surpassed by using materials with lower intrinsic loss. This paper explores dissipation limits in 4H monocrystalline silicon carbide-on-insulator (4H-SiCOI) mechanical resonators fabricated at wafer-level, and reports on ultra-high quality-fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…To examine whether alternative materials could allow for better performing resonators in the future, we consider silicon carbide, [ 48,120,121 ] graphene, [ 15,104,122 ] and diamond, [ 123–125 ] comparing their upper‐bounds of performance relative to silicon nitride. The upper‐bounds are calculated by assuming the material's intrinsic quality factor is the highest experimentally demonstrated to our knowledge at room temperature, [ 121,123,126 ] and their dissipation dilution limit is set by the material yield stress, [ 48,117,127 ] as described in ref. [46].…”
Section: Strain Engineeringmentioning
confidence: 99%
“…To examine whether alternative materials could allow for better performing resonators in the future, we consider silicon carbide, [ 48,120,121 ] graphene, [ 15,104,122 ] and diamond, [ 123–125 ] comparing their upper‐bounds of performance relative to silicon nitride. The upper‐bounds are calculated by assuming the material's intrinsic quality factor is the highest experimentally demonstrated to our knowledge at room temperature, [ 121,123,126 ] and their dissipation dilution limit is set by the material yield stress, [ 48,117,127 ] as described in ref. [46].…”
Section: Strain Engineeringmentioning
confidence: 99%
“…However, there was a consistent discrepancy between our measurement and theoryparticularly in elliptical wineglass modes; this motivated investigation into a new set of elastic constants that better reflect the mechanical properties of 4H-SiC within the framework of the SiCOI platform. As described earlier, achieving high Q is non-trivial often due to anchor losses which rely on a thorough understanding of 4H-SiC's stiffness to conform to various decoupling schemes' stringent frequency requirements [18], [20].…”
Section: B Elastic Anisotropy Refinementmentioning
confidence: 99%
“…The recent development of bond and etch-back thick monocrystalline 4H silicon carbide-on-insulator (4H-SiCOI) substrates [17] and their deep reactive ion etching with high aspect ratio [18], [19] facilitate wafer-level fabrication of capacitive in-plane resonators with ultra-high mechanical Q-factors. Their frequency spectrum measurements have revealed that the elasticity of hexagonal 4H-SiC is not well-understood, evidenced by consistent discrepancy with numerical simulations from wafer to wafer [20].…”
Section: Introductionmentioning
confidence: 99%
“…As a new generation gyroscope, the micro-electro-mechanical system disk resonator gyroscope (MEMS DRG) is an attractive candidate for high-performance MEMS gyroscopes due to its near navigational grade precision and small volume [ 1 , 2 , 3 , 4 , 5 ]. As a solid wave gyroscope (SWG), MEMS DRG inherently possesses a high Q factor and mode match mechanism, which maintain its low mechanical-thermal noise and high mechanical sensitivity [ 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%